The impact of climate change and land use/land cover change on water availability in the Nasia catchment, Northern Ghana. - Tetteh, Josephine (KNUST, 2025)
A Thesis Submitted To The Department Of Geography And Rural Development In Partial Fulfilment Of The Requirements For The Award Degree Of Master Of Philosophy In Geography And Rural Development.